Kate remembered - Berg, A. Scott (Andrew Scott) (New York : Putnam, 2003)
Recounts the remarkable life of leading lady Katharine Hepburn, presenting a portrait of the four-time Academy Award winner through her intimate conversations and private reflections on love, family, friendship, and show business
Keywords: Hepburn, Katharine, -- 1907-2003.; Motion picture actors and actresses -- United States -- Biography